Sub-acute gastric volvulus: a case report. - Paras, KP; Ashish, K; Ashwani, K; Pankaj, G; Nikhil, M (Department of Surgery, UKM Medical Centre, 2013)
Gastric volvulus is a rare condition. Organoaxial gastric volvulus (along longitudinal axis of stomach) occurs acutely, has characteristic symptoms and may be easily detected with upper gastrointestinal (GI) contrast studies. In contrast, subacute, intermittent cases present with intermittent vague symptoms from episodic twisting and untwisting. The main aim of this report was to highlight the fact that early diagnosis and treatment of gastric volvulus should be undertaken to prevent fatal outcome in patients with chronic vague abdominal symptoms.